How to Improve the Validity and Reliability of a Case Study Approach? - Quintão, Cátia; Andrade, Pedro; Almeida, Fernando (Journal of Interdisciplinary Studies in Education, 2021)
The case study is a widely used method in qualitative research. Although defining the case study can be simple, it is complex to develop its strategy. Furthermore, it is still often not considered to be a sufficiently robust research strategy in the education field because it does not offer well-defined and use well-structured protocols. One of the most frequent criticisms associated with the case study approach is its low validity and reliability. In this sense, this study aims to concisely explore the main difficulties inherent to the process of developing a case study, also attempting to suggest some practices that can increase its reliability, construct validity, internal and external validity.